International Efforts for Maintaining International Peace and Security - Mohamed Abdalla Hassan Hamad (International Journal of Law Research and Studies, 2024)
This study examines the international efforts made to maintain international peace and security, as many international efforts were made to establish an effective international organization to maintain international peace and security. As a result a number of conferences were held, and efforts were made to establish the United Nations. A large number of countries participated in establishing the Charter of the United Nations. This demonstrates the extent of international interest and the desire of countries and peoples to maintain international peace and security. There are also political, diplomatic, and judicial means to resolve international disputes by peaceful means that can contribute significantly to maintaining international peace and security if it is implemented.